EDUKASI PENGGUNAAN TABLET FE PADA IBU HAMIL DI KELURAHAN SRENGSEM - Ulfa, Ade Maria; Putri, Anzela Andandya; Rinatha, Elsha; Br Barus, Emia Athena; Rahmawati, Eti (Jurnal Pengabdian Farmasi Malahayati (JPFM), 2023)
Iron deficiency is the primary cause of anemia during pregnancy, which is the most frequent hematological condition among expectant mothers. Pregnant women should be given blood supplement tablets (TTD) in an attempt to prevent iron deficiency anemia. The main factor determining the prevalence of anemia is pregnant women's noncompliance with taking iron supplements. The purpose of this community service project is to raise awareness of the value of eating TTD while pregnant. Seventy expectant mothers who used pre- and post-test questionnaire data gathering methods were the responders. According to the data processing results, respondents in Srengsem Village learned 64.00% more about the significance of taking Fe tablets during pregnancy—that is, before receiving an education.Keywords : Pregnant Women, Drug Use, Fe Tablet Tablets.